Diurnal Variation in Suicide Timing by Age and Gender- A Post-mortem Based Study in New Delhi (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Background: In India, suicide is a national social issue and alone contributes more than 10% of the total suicides in the world. Aim of present study is to find out the diurnal variation in suicide timing in relation to age and gender of suicidal deaths. Material and Method: The present study was conducted in the department of Forensic Medicine and Toxicology, Lady Harding Medical College on a total of 50 cases of suicide brought to the mortuary for post-mortem examination. Result: Most of the victims (52%) were from the age group 21-40 years followed by 12 (24%) from the age group 41-60 years. Maximum incidence (24%) happened between early morning (4 am- 8 am) and late night (12 pm-4 am). In male victims, maximum cases of suicide deaths (28.9%) happened between 4 am to 8 am followed by 23.6% cases between 8 am to 12 pm and 12 am to 4 am. In female victims, maximum cases of suicide deaths (36.3%) happened between 12 pm to 8 pm followed by 27.2% cases between 8 pm to 12 am. Conclusion: In present study, maximum suicides occurred in early morning and late night (24%) followed by late morning (20%).
Keywords: Age; Diurnal variation; Gender; Suicide